Teaching primary mathematical concepts in Chitumbuka: A quest for teacher education - Chauma, Amos (South African Journal of Higher Education, 2016)
In Malawi, Primary school teachers for standards 1 to 4 are trained to teach all subjects except English in Chichewa. However, when they go into the schools they teach in other local languages as well. The paper reports on a study which investigated how primary school teachers in standards 1 to 4 contend with teaching primary mathematical concepts in Chitumbuka. A sample of 12 professionally qualified standards 1 to 4 Chitumbuka speaking primary school teachers from three schools in Rumphi district was used. The study employed qualitative study approach using a case study design. Data was collected through lesson observations, in-depth interviews and focus group discussions. The data was analysed by reading through the transcripts to identify patterns that emerged from the data which were developed into categories. The categories were developed into themes which were interpreted for meaning. The findings revealed that the teachers faced linguistic and pedagogical challenges. However, the teachers devised strategies to cope with the challenges. This study was significant for it revealed the teachers’ lack of mathematical language competence. At present, primary school teachers experience challenges as a result of teaching in a mother tongue in which they were not trained to teach; and a language which differs considerably from the one used in the learners’ textbooks. KEY WORDS: mathematical concepts, coping strategies, case study, pedagogical and linguistic challenges, in-depth interviews, mathematical language competence